The Interacting Amino Acid of Envelope Protein: Exploring the Relationship Between Amino Acid Changes and Pathogenicity in Primate Lentiviruses (Journal of Advances and Scholarly Researches in Allied Education, 2020)
We measured the relative rates of amino acid change, as the ratio of the number of nonsynonymous to synonymous (silent) nucleotide substitutions, for six primate lentiviruses evolving in their respective hosts. These rates for the external envelope glycoprotein (gp120) and gag coding sequences are 2-3 times higher for pathogenic HIV-1 and SIVmac (macaque) than for minimally pathogenic SIVAGM and SIVsmm (sooty mangabey), and intermediate for HIV-2. A spectrum of pathogenicity has been observed for primate lentiviruses in their natural hosts. For example, human immunodeficiency virus type 1 (HIV-1) is a potent etiologic agent for AIDS in man, whereas there is no evidence to date which indicates that simian immunodeficiency virus from African green monkeys (SIVAGM) causes immunodeficiency in AGM. We speculate that the increased rates of nonsynonymous changes in gp120 and gag coding sequences are due to viral escape from immune surveillance and are indicative of higher immunogenicity of these proteins in their hosts. Based on these results and available experimental data, we conclude that there is a positive correlation between lentiviral pathogenicity and immunogenicity of the Env and Gag proteins in a given host. This hypothesis is consistent with recent data suggesting that immune system activation or autoimmunity induced by viral antigens may be important in the pathogenesis of AIDS J Virol. (1987).